Plitidepsin induces apoptosis in glioma cells through β-TrCP-mediated ubiquitination and degradation of BMI1 - Yiting Wei; Yuling Wan; Shilong Duan; Fanyong Gong; Yuewei Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Plastic film mulch mitigates soil respiration by reducing the duration of freeze-thaw transition - Yufei Li; Kaiping Zhang; Wucheng Zhao; Yuling Li; Ningning Zhang; Pingxing Wan; Zhongke Zhou; Jianjun Yang; Hongyuan Kan; Feng Zhang (Soil and Tillage Research, 2026)

Development of a high ethyl hexanoate-producing strain via ARTP mutagenesis and fermentation optimization using agricultural by-products - Yuling Li; Zhiqiang Wang; Renzhi Wan; Xin Zeng; Bingyue Xin; Biao Zhang; Jie Qiao; Deyin Zhao; Mingtao Zhao; Youyu Xie; Zhuangzhuang Jiang; Huawei Zeng; et al. (Biocatalysis and Agricultural Biotechnology, 2026)

Mechanistic insights into isopropyl myristate-stimulated monascus pigment biosynthesis via untargeted metabolomics - Renzhi Wan; Zhiqiang Wang; Yuling Li; Xin Zeng; Bingyue Xin; Jie Qiao; Huawei Zeng; Liang Zhang (World Journal of Microbiology and Biotechnology, 2026)

EGF/ERBB2 blocks the endoplasmic reticulum-associated degradation to facilitate chronic obstructive pulmonary disease development by decreasing FAM8A1 via up-regulating DNMT3A - Ruonan Lv; Jing Wang; Mingrui Wan; Yuling Wang; Yanan Zhang (Functional & Integrative Genomics, 2025)

Identification of the STY13 gene family across the entire genome and an analysis of the essential function of GhSTY13-12 in cotton’s response to abiotic stress - Shaoliang Zhang; Huiyun Shan; Xiaopei Bo; Jiahui Li; Zili Liu; Pengtao Li; Yuling Liu; Xiaojie Yang; Quanwei Lu; Sumei Wan; Renhai Peng; Yangyang Wei; et al. (Functional & Integrative Genomics, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

In-situ air bubble for efficient membrane scaling cleaning with a catalytic nanofiber membrane in membrane distillation - Zhongsen Yan; Ziyue Zhang; Yaman Huang; Haiqing Chang; Dan Qu; Yuling Jiang; Hongting Wan; Senlin Shao; Fangshu Qu (Desalination, 2025)

Temperature sensitivity of soil respiration to elevated temperature and nitrogen availability - Yufei Li; Kaiping Zhang; Yuling Li; Pingxing Wan; Zhongke Zhou; Wucheng Zhao; Ningning Zhang; Ning Chai; Zhixin Li; Yalan Huang; Feng Zhang (Soil and Tillage Research, 2024)

Enhanced generation and effective utilization of H2O2 for simultaneous aging of plastics in the C3N4/Vis-LED system with the addition of phenol - Xiaoman Zhang; Ting Zhang; Hongyang Guo; Shuqi Wan; Xiaodan Liu; Jianhui Sun; Yuling Zhao; Shuying Dong; Xianfa Su; Maohong Fan (Chemical Engineering Journal, 2024)

Plastic film mulching application improves potato yields, reduces ammonia emissions, but boosts the greenhouse gas emissions in China - Yalan Huang; Rongzhu Qin; Huihui Wei; Ning Chai; Yang Yang; Yuling Li; Pingxing Wan; Yufei Li; Wucheng Zhao; Siam Lawawirojwong; Tanita Suepa; Feng Zhang (Journal of Environmental Management, 2024)

Exploring low-carbon mulching strategies for maize and wheat on-farm: Spatial responses, factors and mitigation potential - Huihui Wei; Kaiping Zhang; Ning Chai; Yue Wang; Yuling Li; Jianjun Yang; Matthew Tom Harrison; Ke Liu; Pingxing Wan; Wenjuan Zhang; Guojun Sun; Zhansheng Li; et al. (Science of The Total Environment, 2024)

Alginate-based composites for environmental applications: a critical review - Bing Wang; Yongshan Wan; Yuling Zheng; Xinqing Lee; Taoze Liu; Zebin Yu; Jun Huang; Yong Sik Ok; Jianjun Chen; Bin Gao (Critical Reviews in Environmental Science and Technology, 2019)

Uncovering tea-specific secondary metabolism using transcriptomic and metabolomic analyses in grafts of Camellia sinensis and C. oleifera - Wei-Wei Deng; Jieyun Han; Yanbing Fan; Yuling Tai; Biying Zhu; Mengqian Lu; Rangjian Wang; Xiaochun Wan; Zheng-Zhu Zhang (Tree Genetics & Genomes, 2018)

Construction and characterization of a bacterial artificial chromosome library for Camellia sinensis - Yuling Tai; Hao Wang; Chaoling Wei; Ling Su; Min Li; Liqun Wang; Zhaozhao Dai; Lingyun Shao; Jiayue Jiang; Meizhong Luo; Hua Yang; Weiwei Deng; et al. (Tree Genetics & Genomes, 2017)

Extreme monthly precipitation pattern in China and its dependence on Southern Oscillation - Shiquan Wan; Yuling Hu; Zhiyuan You; Jianpeng Kang; Jianguo Zhu (International Journal of Climatology, 2013)
Using the generalized Pareto distribution (GPD) and a spatial scheme of parameter estimation, spatial patterns of extreme monthly precipitation (EMP) in China were studied using 740 stations' data from 1960 to 2007. The spatial patterns of EMP are described by the GPD's scale and shape parameters, whose regional features depend on ENSO activities. The results show that the scale parameter (representing variability) in monsoon areas, such as southern China, is greater than that of non‐monsoon areas, such as northern China, and that it is greater in summer than that in autumn. The shape parameter (representing record‐breaking probability) reaches a maximum in non‐monsoon areas and a minimum in monsoon areas. For the time scale, record‐breaking events would occur more easily in the seasons other than summer. The regional difference in terms of dependence of EMP's variability on Southern Oscillation (SO) was also related to the monsoon transition zone. The variability with great dependence on SO was in the Qinghai–Tibet Plateau and in the region between the Yangtze and Yellow rivers, which are dry–wet transition zones. The response of EMP's record‐breaking probability to SO is apparent in most regions of China, and its spatial pattern becomes the largest in summer and much smaller in spring and autumn. Copyright © 2012 Royal Meteorological Society